The Role of Biodiversity in Maori Advancement: A Research Framework. - Harmsworth, Garth (He Pukenga Korero: a journal of Māori studies, 2004)
Keywords: biodiversity; environment; planning; sustainable development

Indigenous Māori values and perspectives to inform freshwater management in Aotearoa-New Zealand - Harmsworth, Garth; Awatere, Shaun; Robb, Mahuru (Ecology and Society, 2016)
In response to widespread water quality and quantity issues, the New Zealand Government has recently embarked on a number of comprehensive freshwater management reforms, developing a raft of national discussion and policy documents such as "Freshwater Reform 2013 and Beyond" and a National Policy Statement for freshwater management (NPS-FM 2014). Recent resource management reforms and amendments (RMA 2014), based on previous overarching resource management legislation (RMA 1991), set out a new approach and pathway to manage freshwater nationwide. Internationally, there is an increasing trend to engage with indigenous communities for research and collaboration, including indigenous groups as active participants in resource management decision making. What is driving this change toward more engagement and collaboration with indigenous communities is different for each country, and we document the progress and innovation made in this area in New Zealand. The indigenous rights of Māori in New Zealand are stated in the 1840 Treaty of Waitangi and in many forms of New Zealand's legislation. Local and central governments are eager to include local indigenous Māori groups (iwi/hapū) in freshwater management planning processes through meaningful engagement and collaboration. Key to the success of collaborative planning processes for Māori are enduring relationships between local government and Māori, along with adequate resourcing for all partners contributing to the collaborative process. A large number of shared governance and management models for natural resource management have emerged in New Zealand over the past 20 years, and some recent examples are reviewed. We provide some discussion to improve understanding and use of the terms used in these management models such as cogovernance, comanagement, and coplanning, and describe some of the more important frameworks and tools being developed with Māori groups (e.g., iwi/hapū), to strengthen Māori capacity in freshwater management and to support good collaborative process and planning.
Keywords: co-governance; environment; hapū; iwi; kāwanatanga; local government; mātauranga māori; resource management; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; water management

Māori Values and Perspectives to Inform Collaborative Processes and Planning for Freshwater Management. Landcare Research contract Report No. LC2119. 66p. - Robb, Mahuru; Harmsworth, Garth; Awatere, Shaun (2015)
This report was written in response to the new freshwater reforms and VMO research objectives. The initial research question to be answered was: What is the role of cultural monitoring to inform the collaborative process? This research question was broadened to “provide Māori values and perspectives that inform collaborative processes and planning for freshwater management”, and includes a section on the role of cultural monitoring in collaborative processes. Key objectives were: • Document the Māori historical and legislative context for the collaborative process, including the role of the Treaty of Waitangi • Collate case study information from around New Zealand, on co-governance, co-management and co-planning and define these terms • Provide a range of useful tools to support successful collaboration by Māori and councils in collaborative freshwater management • Identify future challenges.
Keywords: co-governance; tiriti o waitangi/treaty of waitangi; water management

Using mātauranga Māori to inform freshwater management - Harmsworth, Garth; Awatere, S.; Pauling, C. (Landcare Research Policy Brief, 2013)
Keywords: co-governance; environment; governance; hapū; iwi; kāwanatanga; local government; water management

Maori sustainable development in the 21st century: The importance of Maori values, strategic planning and information systems - Harmsworth, Garth; Barclay-Kerr, Kim; Reedy, Tamati (He Puna Korero: Journal of Maori & Pacific Development, 2002)
Keywords: autonomy; economic development; governance; rangatiratanga; self-determination

Indigenous Māori knowledge and perspectives of ecosystems - Harmsworth, Garth R; Awatere, Shaun (Ecosystem services in New Zealand : conditions and trends, 2013)
A framework/model based on Māori knowledge, values and perspectives is presented that distinguishes ‘cultural values’ from ‘cultural services’ and extends the deﬁnition of cultural values across the whole ecosystem services framework. Māori aspirations and well-being are interdependent on ecosystems and ecosystem services. Ultimately Māori wish to use these ecosystem approaches and frameworks to increase participation and inclusion in decision-making, to achieve multidimensional aspirational goals and desired indigenous outcomes.
Keywords: decision making; environment; environmental management; planning; policy making

From hydrology to policy development and implementation: Trends in Aotearoa New Zealand's freshwater management and governance - Fenemor, Andrew; Kirk, Nicholas; Harmsworth, Garth; Taylor, Lara; Weir, Julian; Robson, -Williams Melissa (Journal of Hydrology (New Zealand), 2021)
This section reviews changes to water management and governance in the past ten years. We open with a summary of Aotearoa New Zealand's historical legislative context in regard to rivers, catchments and freshwater resources. We describe the roles of local government, Maori and central government. We detail the growing recognition of tangata whenua values in water management alongside belated development of national policy direction on water quality and allocation. Drawing on the description of modelling advances, we summarise how models are being used in contemporary water management. Finally, we review the implementation of freshwater policy and the integration of science and water policy. In concluding, we argue that integration and implementation challenges must be addressed as hydrologists look beyond 2021 towards future significant legislative changes affecting water and catchment management nationwide.
Keywords: environmental management; policy making; water management

Integrating Indigenous Knowledge and Freshwater Management: An Aotearoa/New Zealand Case Study - Hudson, Maui; Watene-Rawiri, Erina; Robb, Mahuru; Collier, Kevin; Awatere, Shaun; Harmsworth, Garth; Henry, Jacqueline; Quinn, John; Death, Russell; Hamilton, David; Maru, John (The International Journal of Science in Society, 2016)
Keywords: governance; iwi; kāwanatanga; local government; treaty settlements; water management

Where to for collaboration in land and water policy development in Aotearoa New Zealand? Guidance for authorising agencies - Kirk, Nicholas; Robson-Williams, Melissa; Bammer, Gabriele; Foote, Jeff; Butcher, Lian; Deans, Neil; Harmsworth, Garth; Hepi, Maria; Lilburne, Linda; Nicholas, Barbara; Small, Bruce; Turner, James A.; et al. (Kōtuitui: New Zealand Journal of Social Sciences Online, 2022)
For the past decade, collaboration has been the preferred method of devising land and water policy in Aotearoa New Zealand to achieve agreed outcomes. However, the use of collaboration in policymaking is at a crossroads, as some argue it is unrealistic to expect stakeholders and tangata whenua with competing interests to work in partnership on contentious policy issues. To help clarify the future direction of collaboration, this paper provides authorising agencies (those with responsibility for the policy problems) with prompts to reflect ex ante on the advantages and disadvantages of pursuing collaboration. Based on a retrospective review of collaborations in New Zealand’s land and water policymaking, and a two-day symposium with collaboration practitioners, we identify situations that are potentially less suited to collaboration owing to factors that are challenging to overcome through process design. Four issues that affect the success of collaborations are identified: the nature of the policy problem, the personal and collective qualities of those involved, power relationships, and the collaborative process. Finally, we draw together practical lessons from history, the symposium, and the literature to develop a list of questions for authorising agencies to use to reflect on the advantages and disadvantages of pursuing collaboration.
Keywords: co-governance; land policy; policy; water management